PENGARUH INVESTMENT OPPORTUNITY SET, KEPEMILIKAN MANAJERIAL DAN FREE CASH FLOW TERHADAP MANAJEMEN LABA - Velani, Intan Tunandha; Hasanah, Neneng (Jurnal Nusa Akuntansi, 2025)
The research aims to examine the Investment opportunity set, Managerial Ownership, and Free cash flow on Earnings Management in Consumer Non-Cyclical companies listed on the Indonesian Stock Exchange in 2018-2022. The population in this study was 125 companies with observation year 2018-2022. The sample selection in this study used purposive sampling technique. The number of samples obtained was 16 companies with a research year of 5 years, so that 80 observation data were obtained. The data analysis technique used is multiple regression analysis using Eviews 12 software. The results of the research show that the Investment opportunity set, managerial ownership and Free cash flow variables simultaneously influence earnings management. Investment opportunity set partially has no effect on earnings management. Managerial ownership has a significant effect on earnings management. Free cash flow has a negative effect on earnings management.